Enriquecimento alimentar e cognitivo para o bem-estar em cativeiro - COUTINHO, Paulo Henrique Módena (Universidade Federal do Pará, 2014)
When put an animal in captivity, we limit their actions, taking control of most of the variables that act on a restricted environment. These variables, although to remedy the basic needs of the animals has the potential to be highly predictable and therefore stress. Environmental enrichment can be one of the most important advances in animal health in captivity in recent times, raising the psychological and physiological parameters of well-being, suppressed by captivity. The main objective was to create and verify the effectiveness of an environmental enrichment equipment called "roulette" with the function of minimizing the harmful effects of the two captive capuchins, by increasing the time devoted to foraging activities, approaching its budget activities relevant to that of animals in the wild. The observations were made by instantaneous sampling method in five steps: 1) pre-intervention, 2) D5, 3) D10 4) D15 and 5) post-intervention, and subsequently compared longitudinally. The data demonstrate the effectiveness of roulette item enriching the environment, since the behaviors associated with the exploitation and displacement suffered increased over the intervention - with the exception of D10, which will soon be re-evaluated - keeping average frequency of foraging near than expected in free-living animals (Rímoli, 2001) still in the post-intervention observations, rather than the frequency of abnormal behavior or stereotyped.